Penggunaan Kulit Nanas Fermentasi dalam Ransum yang Mengandung Gulma Berkhasiat Obat Terhadap Lemak dan Kolesterol Ayam Broiler - Wasir Ibrahim; Rita Mutia; Nurhayati Nurhayati (Agricultural Faculty, 2015)
(Use of Fermented Pineapple Peel in the Ration Containing Medicinal Weeds on Fat and Cholesterol of Broiler Chicken)ABSTRACT. The objective of the experiment was to determine the effect of using fermented pineapple peel in the ration containing medicinal weeds on fat and cholesterol broiler chicken. The experiment was designed into completely randomized design (CRD) with 5 treatments and 4 replicates. Treatments consisted of P0 = 0% of fermented pineapple peels meal (FPPM) in ration containing 0% medicinal weed (MW), positive control). P1 = 0% of fermented pineapple peels meal (FPPM) in the ration containing 2 % medicinal weed (MW), negative control). P2 = 7,5% of FPPM in the ration containing P1. P3 = 15% of FPPM in the ration containing P1. P4 = 22,5% of FPPM in the ration containing P1. Two hundred 2 days old male broiler chicken were used in this study and kept for 42 days. The parameters were feed consumption, liver weight, bile volume, meat fat level, and meat and blood cholesterol. The observed data were analyzed by Statistical Product and Service Solution (SPSS 16.0) and significant effect among treatments were tested by Duncans Multiple Range Test. The results of thus study showed that the treatments were significant effect (P 0.05) on feed consumption, meat fat of thigh. but were not significant effect (P 0.05) on liver weight, bile volume, meat fat level and meat and blood cholesterol. It is concluded that use of fermented pineapple peel in the ration improved fat and cholesterol on broiler chicken.